Diplomatic Footprints - Chaudhry, Aizaz Ahmad; Ahmad, Sameer (Lahore: Sang-e-Meel Publications, 2021)
Memoirs of Aizaz Ahmad Chaudhry; Pakistani diplomat.
Includes index.
Keywords: Diplomatic and consular service